Disability: concepts and statistical information (Italian Journal of Public Health, 2008)
Background: The measurement and definition of disability is difficult due to its objective and subjectivecharacteristics. In Italy, three different perspectives have been developed during the last 40 years. Thesevarious perspectives have had an effect, not only on how to measure disability, but also on policies to improvethe social integration of people with disabilities.Methods: This paper examines the various conceptual models behind the definition of disability and thedifferences in the estimated number of persons with disabilities. In addition, it analyses in accordance withthe International Classification of Functioning, disability and health, the European and international initiativesundertaken to harmonize the definitions of disability.Discussion: There are various bodies and central government agencies that either have management data orcarry out statistical systematic surveys and disability surveys. Statistically speaking, the worst aspect of thisscenario is that it creates confusion and uncertainty among the end users of this data, namely the policy makers.At international level the statistical data on disability is scarcely comparable among countries, despite hugeefforts on behalf of international organisations to harmonize classifications and definitions of disability.Conclusions: Statistical and administrative surveys provide information flows using a different definition andlabel based on a conceptual model that reflects the time period in which they were implemented. The use ofdifferent prescriptive definitions of disability produces different counts of persons with disabilities in Italy. Forthis reason it is important to interpret the data correctly and choose the appropriate cross section that bestrepresents the population on which to focus attention.
Keywords: definition of disability; statistical surveys; administrative sources